Phenotyping patients with ischaemic heart disease at risk of developing heart failure: an analysis of the HOMAGE trial - Diogo Santos‐Ferreira; Sílvia O. Diaz; João Pedro Ferreira; Nicolas Girerd; Pierpaolo Pellicori; Beatrice Mariottoni; Franco Cosmi; Mark Hazebroek; Job A.J. Verdonschot; Joe Cuthbert; Johannes Petutschnigg; Stephane Heymans; et al. (ESC Heart Failure, 2024)
Abstract Aims We aim to characterize the clinical and proteomic profiles of patients at risk of developing heart failure (HF), with and without coronary artery disease (CAD) or prior myocardial infarction (MI). Methods and results HOMAGE evaluated the effect of spironolactone on plasma and serum markers of fibrosis over 9 months of follow‐up in participants with (or at risk of having) CAD, and raised natriuretic peptides. In this post hoc analysis, patients were classified as (i) neither CAD nor MI; (ii) CAD; or (iii) MI. Proteomic between‐group differences were evaluated through logistic regression and narrowed using backward stepwise selection and bootstrapping. Among the 527 participants, 28% had neither CAD or MI, 31% had CAD, and 41% had prior MI. Compared with people with neither CAD nor MI, those with CAD had higher baseline plasma concentrations of matrix metalloproteinase‐7 (MMP‐7), galectin‐4 (GAL4), plasminogen activator inhibitor 1 (PAI‐1), and lower plasma peptidoglycan recognition protein 1 (PGLYRP1), whilst those with a history of MI had higher plasma MMP‐7, neurotrophin‐3 (NT3), pulmonary surfactant‐associated protein D (PSPD), and lower plasma tumour necrosis factor‐related activation‐induced cytokine (TRANCE). Proteomic signatures were similar for patients with CAD or prior MI. Treatment with spironolactone was associated with an increase of MMP7, NT3, and PGLYRP1 at 9 months. Conclusions In patients at risk of developing HF, those with CAD or MI had a different proteomic profile regarding inflammatory, immunological, and collagen catabolic processes.